Maresin 1 Mitigates Sepsis-Associated Acute Kidney Injury in Mice via Inhibition of the NF-κB/STAT3/MAPK Pathways - Sun, ShuJun; Wang, JiaMei; Wang, JingXu; Wang, FuQuan; Yao, ShangLong; Xia, HaiFa (Frontiers in Pharmacology, 2019)
Acute kidney injury (AKI) is one of the most common and serious complications of sepsis in which the inflammatory cascade plays a crucial role. There is now increasing evidence that lipid mediators derived from the omega-3 fatty acid docosahexaenoic acid (DHA) have potent anti-inflammatory effects that promote the timely regression of acute inflammation. In this study, we investigated the protective effects and molecular mechanism of a novel DHA-derived lipid mediator Maresin 1 (MaR1) on AKI in septic mice. The cecal ligation and puncture (CLP) was used to establish a sepsis mice model. As a result, we found that MaR1 significantly increased the 7-day survival rate of septic mice and the anti-inflammatory factor IL-10 while reducing bacterial load and pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β). In addition, MaR1 dose dependently reduced renal injury scores and serum creatinine and urea nitrogen levels in septic mice while inhibiting renal neutrophil infiltration and myeloperoxidase (MPO) activity. In terms of signaling pathway, we found that MaR1 inhibits the expression of phosphorylated p65, Stat3, JNK, ERK, and p38 and significantly reduces nuclear translocation of p65. In conclusion, our results indicate that MaR1 is able to reduce neutrophil infiltration and inhibit nuclear factor-kappa B/signal transducer and activator of transcriptor 3/mitogen-activated protein kinase (NF-κB/STAT3/MAPK) activity and regulate inflammatory cytokine level to inhibit inflammatory response and thereby weaken sepsis-associated AKI in mice.